The Influence of Al-Qur’an Memory Level and Learning Motivation on Student Academic Achievement - Siti Rohmatin Nur Ifana (Journal of Islamic Education and Ethics, 2023)
The ability to memorize the Qur'an affects one's cognitive intelligence. The students felt the influence of the program provided by UNIRES, which gave birth to a feeling of difficulty in dividing their time between memorizing the Al-Qur'an and following the lecture process in achieving their academic achievements. This situation is also influenced by the motivation to learn. The purpose of this research is; 1) To find out the level of student Al-Qur'an memorization, 2) To find out student learning motivation, 3) To find out student academic achievement, 4) To find out "the mutual influence between the level of Al-Qur'an memorization and learning motivation on the academic achievement of UNIRES students at the University of Muhammadiyah Yogyakarta class of 2021/2022." This research is a quantitative research approach with multiple linear regression research. The research location was at UNIRES UMY. The population is 188 UNIRES students consisting of 70 male students and 118 female students, with a sample of 101 UMY UNIRES students class of 2021/2022. The instrument used is a learning motivation questionnaire and supporting data using interviews. Validity and reliability tests were carried out before the questionnaire was given to the research subjects. Data were analyzed using a multiple linear regression analysis test. The results of this study indicate that there is a simultaneous influence between the level of memorization of the Qur'an and learning motivation on the academic achievement of 2021 UMY UNIRES students. With this research, it is increasingly understood that improvements are needed in the program implementation system, improving the quality of Islamic internalization, the values of Al-Qur'an-based education, and the development of motivation to learn in students.